Assessing Agricultural Literacy Among Senior Secondary School Students in Kwara State, Nigeria: Implications for Educational Interventions - Bature, Shuaib Suleiman; Olorunleke, Adesanya Emmanuel; Ibrahim, Oba Abdulkadir; Kayode, Afolabi Ojo; Bolakale, Jimoh Saidu (Universitas Negeri Semarang, 2023)
This research study aimed to asses the level of agricultural literacy among senior secondary school students in Kwara State, Nigeria, using a descriptive survey research design. The target population comprised all senior secondary school science students in Kwara State, and a sample of 1,200 students was selected using a multi-stage sampling procedure. Data were collected using an adapted standardized questionnaire with a reliability coefficient of 0.71. Both descriptive and inferential statistical analyses were conducted to analyze the data. The findings of the study revealed that there was no significant difference in agricultural literacy among senior secondary school students based on their gender or school location. However, the study did identify a significant difference in agricultural literacy among senior secondary school students based on the type of school they attended. Consequently, the study recommended that agricultural science teachers should focus on other components of agricultural literacy, particularly agricultural policy literacy, to enhance students' understanding of agricultural policy. Abstrak Studi penelitian ini bertujuan untuk mengevaluasi tingkat literasi pertanian di kalangan siswa sekolah menengah atas di Negara Bagian Kwara, Nigeria, menggunakan desain penelitian survei deskriptif. Populasi target terdiri dari semua siswa sekolah menengah atas jurusan sains di Negara Bagian Kwara, dan sampel sebanyak 1.200 siswa dipilih menggunakan prosedur sampel multi-tahap. Data dikumpulkan menggunakan kuesioner standar yang telah diadaptasi dengan koefisien reliabilitas sebesar 0,71. Analisis statistik deskriptif dan inferensial dilakukan untuk menganalisis data. Temuan penelitian ini menunjukkan bahwa tidak ada perbedaan signifikan dalam literasi pertanian di antara siswa sekolah menengah atas berdasarkan jenis kelamin atau lokasi sekolah. Namun, penelitian ini mengidentifikasi perbedaan signifikan dalam literasi pertanian di antara siswa sekolah menengah atas berdasarkan jenis sekolah yang mereka hadiri. Oleh karena itu, penelitian ini merekomendasikan agar guru ilmu pertanian memfokuskan pada komponen literasi pertanian lainnya, terutama literasi kebijakan pertanian, untuk meningkatkan pemahaman siswa tentang kebijakan pertanian.